A combinatorial view of old and new RNA polymerase II modifications. Issue 2 (14th March 2020) - Lyons, Danielle E; McMahon, Sarah; Ott, Melanie
ABSTRACT: The production of mRNA is a dynamic process that is highly regulated by reversible post-translational modifications of the C-terminal domain (CTD) of RNA polymerase II. The CTD is a highly repetitive domain consisting mostly of the consensus heptad sequence Tyr1-Ser2-Pro3-Thr4-Ser5-Pro6-Ser7. Phosphorylation of serine residues within this repeat sequence is well studied, but modifications of all residues have been described. Here, we focus on integrating newly identified and lesser-studied CTD post-translational modifications into the existing framework. We also review the growing body of work demonstrating crosstalk between different CTD modifications and the functional consequences of such crosstalk on the dynamics of transcriptional regulation.